2022
DOI: 10.1001/jamanetworkopen.2022.3064
|View full text |Cite
|
Sign up to set email alerts
|

Age-Varying Susceptibility to the Delta Variant (B.1.617.2) of SARS-CoV-2

Abstract: IMPORTANCEThe Delta variant (B.1.617.2) is estimated to be more transmissible than previous strains of SARS-CoV-2, especially among children and adolescents. However, to our knowledge, there are no reports confirming this to date. OBJECTIVETo gain a better understanding of the association of age with susceptibility to the Delta variant of SARS-CoV-2. DESIGN, SETTING, AND PARTICIPANTS This decision analytic model used an age-structured compartmental model using the terms symptom onset (S), exposure (E), infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…We adapted a previously described model which estimated the age-varying susceptibility to the Delta variant [ 9 ] and updated the model with recent vaccine coverage data and waning of vaccine effectiveness against the Omicron infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adapted a previously described model which estimated the age-varying susceptibility to the Delta variant [ 9 ] and updated the model with recent vaccine coverage data and waning of vaccine effectiveness against the Omicron infection.…”
Section: Methodsmentioning
confidence: 99%
“…Following our previous study, we built an age-structured compartmental model stratified into 5-year age bands [ 9 ]. Compartments in the model were stratified by infection states (i.e., susceptible [ S ], exposed [ E ], infectious and pre-symptomatic [ Ipresym ], infectious and symptomatic [ Isym ], infectious and asymptomatic [ Iasym ], or quarantined [ Q ]), age band, and the transition time to the next infection state (Additional file 1 : eMethods).…”
Section: Methodsmentioning
confidence: 99%
“…(1) random sequence generation, (2) attrition bias, (3) allocation concealments, (4) blinding of participants and personnel, (5) blinding of outcome assessment, (6) incomplete outcome data, (7) selective outcome reporting, and (8) other biases. Each potential source of bias was graded as high, low, or unclear, providing a quote from the study report and a justification of our judgment in the "risk of bias" table.…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…It has also been shown that long-term humoral immune responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children last longer even after asymptomatic infection than in adults (2). At present, the emergence of SARS-CoV-2 variants has caused the increasing prevalence in children around the world (3)(4)(5)(6). More research is urgently needed on the long-term relationship between COVID-19 and children (7).…”
Section: Introductionmentioning
confidence: 99%
“…5 Since we know the age-strati ed incidence of COVID-19 at discrete time, transition time distribution to the next infection stage, and the age-speci c contact matrix for South Korea, we could infer the age-speci c susceptibility using Bayesian inference method (see Methods). [6][7][8][9] More precisely, we removed individuals who were vaccinated from the susceptible population in accordance with the vaccine effectiveness against the Delta and the Omicron variants. 10 The waning of vaccine effectiveness was also considered.…”
mentioning
confidence: 99%